Do Benefit Cuts Boost Job Findings? Swedish Evidence from the 1990s - Kenneth Carling; Bertil Holmlund; Altin Vejsiu (Uppsala University, Department of Economics, 1999)
In June 1995, the Swedish parliament decided to cut the replacement rate in unemployment insurance from 80 percent to 75 percent, a change that took effect on January 1, 1996. This paper examines how this change affected job finding rates among unemployed insured individuals. To identify the effect of the policy we exploit a quasi-experimental feature of the benefit cut: only a fraction of the unemployed was affected by the reduction in replacement rates. We compare the evolution of job finding rates before and after the reform among those affected and those not affected. Our estimates suggest that the reform caused an increase in the transition rate of roughly 10 percent. There is also evidence of anticipatory behavior among the unemployed; the effects of the reform seem to operate several months before its actual implementation in January 1996.
urn:nbn:se:uu:diva-2466
Keywords: J64; J65; 330; Unemployment duration; unemployment benefits; Arbeitslosenversicherung; Arbeitsuche; Dauer; Beschäftigungseffekt; Schweden